Analysis of multiclass pesticide residues in tea using accelerated solvent extraction with in-cell cleanup and gas chromatography tandem mass spectrometry - Abdul Kadir, Haslina (2015)
The application of pesticides in tea plantations is a common practice to control pests and plant diseases. Chemical pesticides are excessively used by the farmers in order to meet the increasing demand for food for the fast growing population. Due to a lack of a proper, continuous and efficient monitoring, farmers are facing severe quality related problems when exporting agricultural products and various problems related to human health being reported. The existing situation urgently demands for the implementation of advanced analytical procedures for accurate monitoring of pesticides in agriculture products and which would be needed for the management of the existing pesticide problem. Therefore, the main objective of this study was to develop an efficient method for analysis of pesticide residues in tea. The current trend in pesticide residue analysis is the use of multiresidue methods that not only provide a simultaneous determination of multiple pesticides but also applicable for analysis of a large number of samples. Despite advances in the development of high performance analytical instrumentation for determination, sample preparation still an important part of obtaining accurate quantitative results. QuEChERS and ASE with in-cell cleanup methods are amongst the modern sample preparation methods developed to overcome the drawback of traditional approach for pesticide analysis. There are many study reported for analysis of multiresidue pesticide analysis using QuEChERS method and the original version of this method also has been modified in order to establish efficient extraction and cleanup procedure for pesticide determination in tea. On the other hand, ASE with in-cell cleanup method has been successfully applied in pesticides analysis but it has not been applied for extraction of pesticides in tea. However, both methods had shown high performance for the analysis of multiresidue pesticides in tea, but their extraction performance based on recovery value was evaluate using spiked sample. Unlike incurred sample, the pesticide in spiked samples only coats the surface of matrices and may not be bound up in the tea cell structure. The first part of this study is to compare the extraction efficiencies of the QuEChERS and ASE with in-cell cleanup methods by using the reference material of incurred pesticide in tea. The extracts were analysed by gas chromatography-tandem mass spectrometry (GC-MS/MS). Following this, the selected method for analysis of multiresidue pesticides in tea was validated and subsequently apply to determine the occurrence of pesticides in tea samples. In addition, the uncertainty of pesticides measurement using ASE with in-cell cleanup method was also quantified and estimated based on top down approach. ASE with in-cell cleanup method gave an average recovery of 91% with a 17% RSD whereas the QuEChERS method gave an average recovery of 64% with a 18% RSD. The recovery obtained from the QuEChERS method was outside the requirement set by the validation guidelines implying that the method is not reliable for extraction of pesticides in tea. Therefore, the ASE with in-cell cleanup method was selected and further validate for sample preparation of multiresidual pesticide analysis of a real sample. ASE with in-cell cleanup method was applied for the validation extraction of multiresidue pesticides comprising endosulfan, lindane, dieldrin, chlorpyrifos and bifenthrin. Method validation parameters such as the linearity, limits of detection and quantification, recovery, precision and accuracy of the method for all of the pesticides studied were carried out. Linear correlation coefficients for all of the tested pesticides were better than 0.995. The overall average recoveries using this method at three spiked concentration of 0.04, 2.0 and 3.5 μg g-1 ranged from 90 to 98%, and the relative standard deviations (RSDs) were less than 10% for all of the analytes. The limits of detections (LODs) ranged from 0.001 to 0.007 μg g-1, and the limits of quantifications (LOQs) ranged from 0.009 to 0.021 μg g-1. The results obtained from the validation parameters suggested that the ASE with in-cell cleanup method has good purification effect and therefore, resulting in a better detection and quantification by the GC-MS/MS. This method was subsequently applied to ten different brands of tea samples obtained from a local supermarket. The concentration of pesticide residues in all samples were detected to be lie in the range of 0.008 to 0.161 μg g-1. The uncertainty in the measurement of each pesticide was also evaluated. The measurement uncertainty (MU) was used to decide whether the results indicate compliance or non-compliance with the maximum residual limits (MRLs) value. Two out of ten samples were found noncompliance with European Union’s regulation. The relative expanded uncertainty for all pesticides were ranged from 24 to 34% and were considered as satisfactory for routine analysis. The incurred pesticide in a complex matrix such as tea makes it difficult to obtain complete extraction of pesticides. However, the combination of high temperature and pressure of ASE with in-cell cleanup method results in better extraction efficiency. The built-in features of this method allow short time sample extraction and less solvent used compared with the QuEChERS and other methods developed for pesticide analysis. The convenience, simplicity and reliability of the ASE with in-cell cleanup method is undoubtedly makes it a valuable tool for analysis of multiresidue pesticides in other agricultural products and can be applied as a routine method.